2015
DOI: 10.1016/j.taap.2015.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to quantum dot induced lung inflammation differs widely among the Collaborative Cross founder mouse strains

Abstract: Quantum dots (QDs) are engineered semiconductor nanoparticles with unique physicochemical properties that make them potentially useful in clinical, research and industrial settings. However, a growing body of evidence indicates that like other engineered nanomaterials, QDs have the potential to be respiratory hazards, especially in the context of the manufacture of QDs and products containing them, as well as exposures to consumers using these products. The overall goal of this study was to investigate the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 73 publications
0
29
0
Order By: Relevance
“…The authors quantified dosimetric doses of cadmium (Cd) mass in the lungs of these differentially sensitive genotypes and detected higher burdens in A/J mice compared to C57BL/6J mice, suggesting that airway physiology (marked by alveolar size and airway branching) may be a contributing factor in genotype effects on QD toxicity-which may be broadly applicable to other types of ENM, such as AgNP. 42,66,67 With regard to host acquired factors, Chuang et al treated OVA-sensitized, female BALB/cJ mice by inhalation and observed antigen effects on AgNP-induced oxidative stress in allergic mice compared to healthy mice and fresh air controls, with allergic and healthy mice being differentially sensitive to AgNP toxicity. 68 In a similar study, Alessandrini et al exposed OVA-sensitized, female BALB/cJ mice by tracheal instillation and observed size, coating, dose, and antigen effects on AgNP-induced T2 lung inflammation in allergic mice compared to healthy mice and vehicle controls, with allergic and healthy mice also being differentially sensitive to AgNP toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors quantified dosimetric doses of cadmium (Cd) mass in the lungs of these differentially sensitive genotypes and detected higher burdens in A/J mice compared to C57BL/6J mice, suggesting that airway physiology (marked by alveolar size and airway branching) may be a contributing factor in genotype effects on QD toxicity-which may be broadly applicable to other types of ENM, such as AgNP. 42,66,67 With regard to host acquired factors, Chuang et al treated OVA-sensitized, female BALB/cJ mice by inhalation and observed antigen effects on AgNP-induced oxidative stress in allergic mice compared to healthy mice and fresh air controls, with allergic and healthy mice being differentially sensitive to AgNP toxicity. 68 In a similar study, Alessandrini et al exposed OVA-sensitized, female BALB/cJ mice by tracheal instillation and observed size, coating, dose, and antigen effects on AgNP-induced T2 lung inflammation in allergic mice compared to healthy mice and vehicle controls, with allergic and healthy mice also being differentially sensitive to AgNP toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…We derived organotypic cultures from primary murine tracheal epithelial cells (MTEC) of differentially sensitive genotypes (A/J and C57BL/6J mice) to model the effects of host genetic factors on AgNP toxicity. [41][42][43] We then differentiated these organotypic cultures toward either "Normal" or "Type 2 [T2]-Skewed" phenotypes to model the effects of host acquired factors on AgNP toxicity. To acquire the "Normal" phenotype, we used a defined differentiation media to achieve differentiation toward the cell populations in the proximal region of the conducting airway, including basal, ciliated, club, and mucin cells.…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophils are key cells in acute inflammatory responses, and, accordingly, we have used neutrophil influx as a primary marker of ENM-induced lung inflammation in previously published studies (46,47). Therefore, we used neutrophil influx as the phenotype of interest in this study, which was focused on identifying genetic determinants of AgNP-induced lung inflammation.…”
Section: Lung Inflammationmentioning
confidence: 99%
“…Furthermore, phenotype data are available for several focus areas e.g., immunology (Phillippi et al 2014), morphology (Percival et al 2016), behavior (Logan et al 2013) and intestinal microbiota (Campbell et al 2012). Also, founder strains were subjected to multiple challenges such as susceptibility to quantum dot (Scoville et al 2015), response to microbiological (Smith et al 2016) and viral Leist et al 2016) infections. In this context, investigations of the pre-CC strains were often carried out as well Gralinski et al 2015;Kelada 2016;Kelada et al 2012;Phillippi et al 2014;Rutledge et al 2014).…”
Section: Introductionmentioning
confidence: 99%